2-Bromo-1-(1-phenylsulfonyl-1H-indol-3-yl)propan-1-one - C. Ramathilagam; P. R. Umarani; V. Saravanan; A. K. Mohanakrishnan; B. Gunasekaran; V. Manivannan (Acta Crystallographica Section E, 2014)
In the title compound, C17H14BrNO3S, the phenyl ring makes a dihedral angle of 89.78 (16)° with the plane of the indole ring system. The terminal Br atom and the methyl group are disordered over two sets of sites, with site occupancies of 0.860 (2) and 0.140 (2). In the crystal, molecules are linked into a chain along the b-axis direction by weak C—H...O hydrogen bonds. The chains are further linked by C—H...π interactions, forming layers parallel to the bc plane.